Förslag till bebyggelse och park i kvarteret Seminariet i Uppsala - Ellwén, Karin (2010)
In the urban planning debate of today, two strategies for city development stand out as each other's opposites, urban sprawl and smart growth. This thesis concerns a development project of the latter kind and aims to give an alternative proposal to new buildings and a park in a Swedish city block.